GROWTH, FRUITING CYCLE AND OOSPORE OUTPUT IN TURBINARIA DECURRENSBORY - Kaliaperumal, N; Rao, M Umamaheswara (Indian Journal of Fisheries, 2011)
iStudies oil the growth, fruiting cycle and oospore output in Turbinariadecurrens, carried out for one year from March 1972 to February 1973 are presentedin this papsr. Young plants of T. decurrens, observed in the natural habitatsin May and June, grow to maximum size in the period from December to February.Plants with receptacles occur for eleven months from August to June, with largenunibsr of fruiting plants in the peak growth season from December to February.Periodicity was not seen in the liberation of oospores and during the fruitingseason peak output erf spores was observed in November. From this study, it issuggested that the period December-January is suitable for harvesting the cropof T. decurrens in the localities around Mandapam.